Optimizing the co-benefits of biodiversity and carbon sinks in urban residential yards - Ariluoma, Mari; Kinnunen, Antti; Lampinen, Jussi; Hautamäki, Ranja; Ottelin, Juudit (Frontiers in Sustainable Cities, 2024)
Urban green infrastructure is recognized for its potential to combat biodiversity loss and enhance carbon sequestration in cities. While residential yards constitute a significant part of urban green infrastructure, their role in providing urban ecosystem services remains largely understated. There is a lack of systematic measures for effectively implementing urban vegetation to enhance ecosystem services. The aim of this study is to investigate how different vegetation types typically found in urban residential yards of apartment blocks can enhance carbon sequestration and biodiversity, and how these benefits can be supported through landscape design. The study encompasses an integrative literature review and qualitative analysis. Drawing from a review of previous research, this study identifies the drivers that indicate either carbon sink potential or biodiversity enhancement potential of urban vegetation types. The drivers are then cross-examined to identify the qualities of urban green that potentially strengthen carbon–biodiversity co-benefits. As the key findings we present versatile measures to enhance the potential co-benefits of carbon sinks and biodiversity within urban yards and summarize them in three main categories: plant diversity, provision of good growing conditions and maintenance. The study stresses that the several potential co-benefits of urban green can only be achieved through the selection and prioritization of solutions during the planning and design process. To exemplify this, we demonstrate how the findings from the literature review can be incorporated into the design and management of urban yards. We conclude that the main actions to be addressed in the future planning and design of urban residential yards are (i) establishing diverse planting areas with a mixture of woody and herbaceous plants to encourage species richness and complexity, (ii) optimizing the use of space and growth conditions, and, (iii) implementing maintenance practices that consider both carbon and biodiversity aspects. The study highlights that through enhancing carbon-biodiversity co-benefits urban yards can significantly contribute to major environmental challenges and provide vital ecosystem services within the built urban environments.